Aktivitas Antidiabetes Pada Senyawa Viteksin Kombucha Bunga Telang (Clitoria ternatea L) Melalui Studi Bioteknologi Komputasi (Bioinformatika) - Merdiana Indah Saputri; Renni Dwi Saputri; Firman Rezaldi; Ratna Fitry Yenny; Roihwan Roihwan; Hadi Susilo (Sekolah Tinggi Ilmu Kesehatan Tujuh Belas, Karanganyar, JAwa, Indonesia, 2024)
Increased and uncontrolled glucose levels are one of the early symptoms of diabetes mellitus. Based on the cause, diabetes mellitus is classified into two, namely type 1 and type 2 diabetes. Diabetes causes damage to body organs such as kidney failure, heart failure, eye cataracts, and even death. Diabetes management consists of 3 types, namely short-term, long-term and final goals. The link protein that plays an important role as a receptor in synthesizing glucose in the body as a cause of diabetes mellitus is GSK?3. The glucose-forming receptors in the body need to be inhibited by the bioactive compounds found in butterfly pea flower kombucha in the form of vitexin from the flavonoid group in silico. In previous research, the vitexin compound in butterfly pea flower kombucha has been proven to have potential as an anti-allergy, antioxidant and anticancer in silico, so in this study it has also been proven that the vitexin compound in butterfly pea flower kombucha with the 5HG7 ligand as the target protein can bind to the GSK?3 receptor. The lowest binding affinity value produced in this study was -6.5, so it can be concluded that the vitexin compound contained in telang flower kombucha can be used as a new drug candidate to prevent diabetes.